2016
DOI: 10.1038/onc.2016.240
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 promotes prostate cancer via MMP7-induced epithelial-to-mesenchymal transition

Abstract: Chronic inflammation has been associated with a variety of human cancers including prostate cancer. Interleukin-17 (IL-17) is a critical pro-inflammatory cytokine, which has been demonstrated to promote development of prostate cancer, colon cancer, skin cancer, breast cancer, lung cancer, and pancreas cancer. IL-17 promotes prostate adenocarcinoma with a concurrent increase of matrix metalloproteinase 7 (MMP7) expression in mouse prostate. Whether MMP7 mediates IL-17’s action and the underlying mechanisms rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 59 publications
(85 reference statements)
8
138
0
Order By: Relevance
“…This also indicates that MMP-7 acts as an upstream signal for EMT responses. Consistent with our findings, MMP-7 knockout mice exhibited decreased EMT and metastasis in a mouse model of prostate carcinoma (38). Similar to the present report, other studies have also demonstrated MMP-7-mediated cleavage of cell-cell adherent proteins including E-cadherin and zona occludin-1 in different cancer models (14,29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This also indicates that MMP-7 acts as an upstream signal for EMT responses. Consistent with our findings, MMP-7 knockout mice exhibited decreased EMT and metastasis in a mouse model of prostate carcinoma (38). Similar to the present report, other studies have also demonstrated MMP-7-mediated cleavage of cell-cell adherent proteins including E-cadherin and zona occludin-1 in different cancer models (14,29).…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the present report, other studies have also demonstrated MMP-7-mediated cleavage of cell-cell adherent proteins including E-cadherin and zona occludin-1 in different cancer models (14,29). Furthermore, MMP-7 disrupts the E-cadherin-b-catenin complex, causing the release of b-catenin, which also promotes EMT in human prostate cancer cells (38).…”
Section: Discussionsupporting
confidence: 90%
“…MMP7 is a matrix metallopeptidase that is involved in tumour progression by influencing cell invasion, metastasis, and the epithelial-to-mesenchymal transition [2123]. It is well known that MMP7 is a downstream target of the Wnt/β-catenin signalling pathway that is activated in multiple cancers including breast cancers [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that certain pro-inflammatory factors can up-regulate PD-L1 expression, including interferon-γ (IFN-γ), tumor necrosis factor – α (TNF-α), lipopolysaccharide, granulocyte-monocyte colony stimulating factor, vascular endothelial growth factor, interleukin-10 (IL-10), and IL-4, with IFN-γ being the most potent inducer [16]. Interleukin-17 (IL-17, also called IL-17A) is a key pro-inflammatory cytokine that has been shown to promote prostate and colon cancer development [1720]. IL-17 and TNF-α have been shown to cooperate functionally to induce expression of down-stream genes [21].…”
Section: Introductionmentioning
confidence: 99%